Underpricing Determinants on the Public Offering of Primary Shares (IPO) in Indonesia Stock Exchange 2015-2019 - Kirana Astuti, Diah; Djamaluddin, Said (Dinasti Publisher, 2021)
This study aims to obtain empirical evidence about the influence of Underwriter's Reputation, Return On Assets, Company Age, Company Size, Debt to Equity Ratio on Underpricing. The independent variables used in this study are Underwriter's Reputation, Return On Assets, Company Age, Company Size, Debt to Equity Ratio. The dependent variable used in this study is underpricing which is measured by initial return. This research was conducted on companies that made initial public offerings (IPO) from 2015-2019 on the Indonesia Stock Exchange. Sampling was done using purposive sampling method resulting in 114 companies as the research sample. The results of this study indicate that the Underwriter's Reputation and Debt to Equity Ratio variables have an effect on Underpricing. Meanwhile, Return On Asset, Company Age, Company Size have no effect on Underpricing. So an underwriter with a good reputation can reduce the level of underpricing and not result in loss of additional capital receipts for the company. And the higher the DER, the higher the level of underpricing. Because companies with high DER indicate a high risk of failure for the company and will influence public or investors interest in investment decision makers.